KONTRIBUSI PELAKSANAAN PEMBELAJARAN KEWIRAUSAHAAN DAN INTERAKSI SOSIAL TERHADAP KARAKTER KEWIRAUSAHAAN PESERTA DIDIK MAN 1 PEKANBARU - Atikah Hermansyah; Daeng Ayub Natuna; Sumarno Sumarno (PEKBIS, 2017)
The purpose of this study is to determine the contribution of the implementation ofentrepreneurial learning and social interaction, either individually or jointly to theentrepreneurial character of learners. This study was conducted in MAN 1Pekanbaru. The population in this study were students of class XI and XII IPS IIS asmany as 139 respondents with prior test instrument by 30 respondents. Testing thevalidity of the correlation performed using SPSS software and instrument reliabilityseen in Alpha Croncbach. This research was conducted with a descriptiveexamination of data, testing hypotheses and seek contributions. The result ofresearch shows that 1) Contributions implementation of entrepreneurial learningentrepreneurial character by 20%. 2) The contribution of social interaction with theentrepreneurial character of 11.5%. 3) Contributions implementation ofentrepreneurial learning and social interaction with the entrepreneurial character ofstudents was 22.1,%. The conclusion that the implementation of entrepreneuriallearning and social interaction with the entrepreneurial character of learners MAN 1Pekanbaru ties and contributions.